Employee Empowernment And Innovation: Fostering A Culture Of Creativity In The Workplace - Siddiqui, Aaiman (Universitas Islam Kadiri, 2025)
The study aims to explain the relationship between employee empowerment, Innovation and creativity. The study comprises of three foundational variables that are Employee empowerment, innovation and creativity, and the association of employee empowerment with innovation and creative. The results indicate that 32.33% of the respondents did not think that the university's organizational culture was empowering. Furthermore, 37% of the participants believed that faculty members' titles had an impact on their ability to make and accept decisions. Further, the findings indicate that 2% of respondents strongly agreed with the statement, 2% agreed with it, and 2% were motivated to establish innovative and cutting-edge techniques for creating lecture plans and related activities in their organization, according to the findings. The conclusion indicates that the organization's demotivating environmental conditions impede innovation and créativité. The findings of the study suggest that corporate culture has a substantial effect on employees' mental health and, if not in the appropriate way, causes stress in workers. The relationship between commitment and organizational culture, subculture, leadership style and job satisfaction in organizational change and development.